2, 4-D exposure and urinary markers of oxidative DNA damage and lipid peroxidation: a longitudinal study. (29th January 2020) - Lerro, Catherine Chase; Andreotti, Gabriella; Wong, Jason YY; Blair, Aaron; Rothman, Nathaniel; Beane Freeman, Laura E
Abstract : Objective: 2, 4-Dichlorophenoxyacetic acid (2, 4-D) is a herbicide that is commonly used commercially, agriculturally and residentially worldwide. There is concern about its potential for carcinogenicity based on studies in laboratory animals demonstrating the potential for induction of oxidative stress. We conducted a longitudinal biomarker study of 31 pesticide applicators in Kansas who heavily applied 2, 4-D and 34 non-applicator controls. Methods: We used multivariable generalised linear mixed-effect models to evaluate the association between urinary 2, 4-D and natural log-transformed 8-iso prostaglandin F2α (8-isoprostane) and 8-hydroxy-2'-deoxyguanosine (8-OHdG), adjusting for urinary creatinine, age, tobacco use and concomitant use of the herbicide picloram. Results: Compared with non-applicator controls, urinary 2, 4-D in the third quartile of exposure was associated with elevated 8-isoprostane ( e β =1.38, 95% CI 1.03 to 1.84). There was no association among the highest exposed and no exposure-response trend. 2, 4-D exposure was not associated with 8-OHdG. Results were unchanged when restricted to participants who only applied 2, 4-D (no picloram use). Conclusions: We did not find evidence that increasing 2, 4-D exposure was associated with 8-isoprostane or 8-OHdG. Future work should carefully evaluate potential confounders of this association, such as diet and physical activity, as well as additional biological markers of oxidative stress and damage.